2012
DOI: 10.1016/j.neuron.2012.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Microstimulation Activates a Handful of Muscle Synergies

Abstract: SUMMARY Muscle synergies have been proposed as a mechanism to simplify movement control. Whether these coactivation patterns have any physiological reality within the nervous system remains unknown. Here we applied electrical microstimulation to motor cortical areas of rhesus macaques to evoke hand movements. Movements tended to converge towards particular postures, driven by synchronous bursts of muscle activity. Across stimulation sites, the muscle activations were reducible to linear sums of a few basic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
245
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(267 citation statements)
references
References 40 publications
20
245
2
Order By: Relevance
“…Finally, in apparent contrast with previous observations in monkey (2)(3)(4), in the present study, we did not identify complex neural representations for other ethologically relevant behaviors (e.g., defensive, manipulative) besides hand/mouth synergies. This could be taken as an indication that such representations do not exist in the human PrG, at least in the region we stimulated, but this hypothesis is unlikely.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Finally, in apparent contrast with previous observations in monkey (2)(3)(4), in the present study, we did not identify complex neural representations for other ethologically relevant behaviors (e.g., defensive, manipulative) besides hand/mouth synergies. This could be taken as an indication that such representations do not exist in the human PrG, at least in the region we stimulated, but this hypothesis is unlikely.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the generality of this model was recently challenged in nonhuman primates, where reaching, grasping, defensive, and hand/mouth movements have been found to be represented as complex motor primitives in independent circumscribed territories of the precentral gyrus (PrG) (2)(3)(4). To account for this observation, it was suggested that complex motor primitives have emerged during primate evolution to optimize the production of ethologically relevant behaviors (4).…”
mentioning
confidence: 99%
“…It seems likely that the spatial scale of clinical stimulation (5 mm) might result in movements closer to the tonic/seizure end of the spectrum, whereas microstimulation (~ 1 mm) may produce finer movements closer to the behavioral end of the spectrum. 8,9,16 Just as in previous human and animal stimulation studies, the observed responses were stereotyped across subjects, allowing for easy classification in most cases.…”
Section: Discussionmentioning
confidence: 80%
“…8 Further support comes from work by Overduin et al, demonstrating that microstimulation-evoked electromyographic patterns in macaques can be decomposed into smaller sets of muscle synergies that closely mirror those generated by natural hand movements. 16 Whether our observed movements are behaviorally relevant is unclear. It seems likely that the spatial scale of clinical stimulation (5 mm) might result in movements closer to the tonic/seizure end of the spectrum, whereas microstimulation (~ 1 mm) may produce finer movements closer to the behavioral end of the spectrum.…”
Section: Discussionmentioning
confidence: 94%
“…The laws governing these primitives are constrained by the structure of the muscular system, and the neural systems that control our movements where motor synergies seem to play a major role [59]. Several computational motor control theories incorporate a notion of motor cost in one way or another.…”
Section: The Costs Of Non-verbal Communication Within Social Interactmentioning
confidence: 99%